2014
DOI: 10.1080/01635581.2015.967874
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Low-Fat Dairy Products and Energy and Protein Intake in Cancer Patients at Risk of Malnutrition

Abstract: Current nutritional guidelines encourage the reduction of fat intake from animal sources like dairy products. The aim was to determine whether the consumption of low-fat dairy is related to poorer dietary intake and nutritional status in cancer patients at risk of malnutrition. This cross-sectional included patients with solid or hematological malignancies at risk of malnutrition. Nutritional status was studied using Subjective Global Assessment, anthropometry, and grip strength. Dietary intake was evaluated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Previous studies have assessed the dietary intake of oncological patients, mainly focusing on energy and macronutrients intake. Specifically, dietary energy intakes of patients with advanced malignant disease have been previously reported (Bauer et al, 2005a;Bauer and Capra, 2005b;Bosaeus et al, 2001;DeWys et al, 1981;Fearon et al, 2003;Menon et al, 2014;Vidal-Casariego et al, 2015) with average energy intakes ranging between 22 and 24 kcal/kg/day, while higher intakes (25!35 kcal/kg BW) seem to be required for weight maintenance (Baracos, 2006). Regarding protein intakes, previous studies reported a protein intake of <1.5 g/kg/day (Hutton et al, 2006;Vidal-Casariego et al, 2015).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies have assessed the dietary intake of oncological patients, mainly focusing on energy and macronutrients intake. Specifically, dietary energy intakes of patients with advanced malignant disease have been previously reported (Bauer et al, 2005a;Bauer and Capra, 2005b;Bosaeus et al, 2001;DeWys et al, 1981;Fearon et al, 2003;Menon et al, 2014;Vidal-Casariego et al, 2015) with average energy intakes ranging between 22 and 24 kcal/kg/day, while higher intakes (25!35 kcal/kg BW) seem to be required for weight maintenance (Baracos, 2006). Regarding protein intakes, previous studies reported a protein intake of <1.5 g/kg/day (Hutton et al, 2006;Vidal-Casariego et al, 2015).…”
Section: Discussionmentioning
confidence: 98%
“…Specifically, dietary energy intakes of patients with advanced malignant disease have been previously reported (Bauer et al, 2005a;Bauer and Capra, 2005b;Bosaeus et al, 2001;DeWys et al, 1981;Fearon et al, 2003;Menon et al, 2014;Vidal-Casariego et al, 2015) with average energy intakes ranging between 22 and 24 kcal/kg/day, while higher intakes (25!35 kcal/kg BW) seem to be required for weight maintenance (Baracos, 2006). Regarding protein intakes, previous studies reported a protein intake of <1.5 g/kg/day (Hutton et al, 2006;Vidal-Casariego et al, 2015). In our study, mean energy and protein intake were estimated at 27 kcal/kg/day and 1.2 g/kg/day, respectively, and 6 out of 10 patients did not reach the goal for energy and/or protein intake, showing a compromised dietary intake even before the initiation of the systematic anticancer therapy.…”
Section: Discussionmentioning
confidence: 98%